Detection threshold of distorted self-avatar step length during gait and the effects on the sense of embodiment - Willaert, Iris; Aissaoui, Rachid; Vallageas, Valentin; Nadeau, Sylvie; Duclos, Cyril; Labbe, David R. (Frontiers in Virtual Reality, 2024)
In immersive VR, a self-avatar that replicates the user’s movements and is viewed from a first-person perspective can substitute the real body. If the avatar’s movements are sufficiently synchronized with the user’s actual movements, the user can experience a sense of embodiment over the avatar. Recent studies have shown that discrepancies between the movements of the avatar and those of the user can be well tolerated while maintaining high levels of embodiment. The point at which a distortion is perceived (detection threshold) and its impact on the level of embodiment has not been studied in lower limb tasks such as gait. This study aimed to identify a detection threshold of gait asymmetry by unilaterally manipulating the step length of a self-avatar, and the effect of this detection on perceived embodiment. A real-time step length distortion model was developed, and a detection threshold between actual and avatar’s gait movement was assessed on thirty healthy participants. The step length was manipulated to introduce gait asymmetry (ascending condition) or start from a large asymmetry that was gradually decreased (descending). The results showed that, on average, the avatar’s step length could be increased by up to 12% before the participants detected the distortion. Furthermore, in the descending condition, they detected increases that were above 9%. The point of detection had no effect on the sense of embodiment as participants still reported being embodied in their avatars, even when they consciously detected the step length distortion. The sense of embodiment was closely correlated with the level of distortion; as distortion increased, embodiment decreased, and vice versa. For a given distortion level, embodiment was similar whether in the ascending or descending condition. This suggests that embodiment can be achieved even when the avatar’s spatial alignment initially differs from the participants’, provided that alignment is gradually restored. These results provide valuable insights into participants’ ability to tolerate movement discrepancies in embodied avatar experiences during gait in virtual environments, with potential applications in motor training and gait rehabilitation.